Culture wars in Brazil: The far-right and their failure to protect cultural heritage. (June 2023) - Kerr, John
Far-right politicians in Brazil are attacking and censoring cultural heritage and enacting policies that go far beyond cultural heritage. These politicians are also dismantling the structural frameworks that protect, secure, encourage and enable cultural heritage at a time when it is experiencing serious and systematic crime threats. This is despite legal obligations in the Brazilian Constitution to protect it. In addition, these politicians are missing opportunities in the sector from which they could benefit hugely, as could the Brazilian population and the cultural heritage. Instead of waging 'culture wars', politicising security, and failing to adequately protect cultural heritage, a viable alternative is to govern the cultural economy.